(untitled) (Fiep Bulletin - online, 2013)
This paper aims to examine the body from concepts and values of scientific rationality. In this reasoning, the manipulation was intended to bodies that do not have the scientific aspect of our society and the pattern desired in education, physical education and sports. Thus, the mind won symbolized by the body so self-competitive behavior that was manifested in the social environment of those glorious dispute within this broken process and all other bodies that were not the same image. The proposed change in paradigm to recast the values is a possibility based on the assumptions of the complexity of MORIN (2005), the body of Santin (1992) and MOREIRA and SIMÕES (2006) and the ecology of deep CAPRA (1999), in search a balance of values. The complexity, the body and deep ecology will lead to expansion of new thoughts, to understand the social dynamics and its contradictions. The change of paradigm on top of the figures is a path in search of respecting diversity among all beings on this planet